Seeking refuge : Central American migration to Mexico, the United States, and Canada - García, María Cristina, 1960- (University of California Press, 2006)
In this incisive book, María Cristina García tells the story of the migration caused by the political upheaval in Nicaragua, El Salvador, and Guatemal and the resulting domestic and foreign policy interests that shaped the asylum policies of Mexico, the United States, and Canada.